Analisa Kebutuhan Sebagai Konsep Dasar dalam Pengembangan Kurikulum Bahasa Arab di MAN Curup - Nurjannah, Nurjannah (Sekolah Tinggi Agama Islam (STAIN)Curup, 2018)
Needs analysis in curriculum development is necessary to assess and identify the needs of Arabic and community teachers in curriculum development, as curriculum development is essentially oriented to the needs of Arabic language teachers and the needs of the community, including the needs of the subject. Needs analysis is also used to identify the incompatibility between the performance of the desired Arabic teacher and the performance of the real Arabic teacher. In the school system Needs analysis is needed to find curriculum deficiencies that involve school community collaboration and understanding of school programs for improvement. The purpose of the curriculum needs analysis is to find the right solution to solve the curriculum problem. One of the basic assumptions of curriculum development in education should be based on student needs analysis. The procedure used to collect information about student needs is known as needs analysis. The method of needs analysis in curriculum development is made to be able to measure the level of gap that occurs in student learning from what is expected and what has been obtained. The conclusions obtained in the analysis are: the needs of the curriculum is a formal process to determine the distance or gap between what exists and how should be from a curriculum, the priority of the main problem and then solved the problem. Needs analysis is a constructive and positive tool for making changes based on rational logic, functional changes that can meet the needs of citizens, groups and individuals.